Design, synthesis and biological evaluation of novel human monoamine oxidase B inhibitors based on a fragment in an X-ray crystal structure. Issue 8 (15th April 2019) - Cheng, Kai; Li, Shiyu; Lv, Xiao; Tian, Yongbin; Kong, Haiyan; Huang, Xufeng; Duan, Yajun; Han, Jihong; Xie, Zhouling; Liao, Chenzhong
Graphical abstract: Highlights: Novel reversible selective hMAO-B inhibitors were designed from a fragment, isatin. Five different scaffolds were designed and many compounds were synthesized. Compound A3 demonstrated very high potency and isoform selectivity against hMAO-B. Our results may challenge our understanding of molecular interactions. Abstract: Herein we report our efforts of developing reversible selective hMAO-B inhibitors based on isatin, a fragment in an X-ray crystal structure. Five different scaffolds were designed and many compounds were synthesized. Among them, compound A3 demonstrated very high potency and isoform selectivity against hMAO-B, 11 and 13 times more potent (IC50  = 3 nM) and 23.64 and 6.8 times more selective than the marked drugs, selegiline and safinamide. However, the endeavors to modify the polar 3-one group of isatin, that is in a hydrophobic environment in the binding site of hMAO-B, to small nonpolar hydrophobic groups did not bring about improved hMAO-B inhibitors, which may challenge our understanding of molecular interactions and molecular recognition in biological systems.